An innovative cycling exergame to promote cardiovascular fitness in youth with cerebral palsy. (3rd March 2016) - Knights, Shannon; Graham, Nicholas; Switzer, Lauren; Hernandez, Hamilton; Ye, Zi; Findlay, Briar; Xie, Wen Yan; Wright, Virginia; Fehlings, Darcy
Abstract: Objective : To evaluate the effects of an internet-platform exergame cycling programme on cardiovascular fitness of youth with cerebral palsy (CP). Methods : In this pilot prospective case series, eight youth with bilateral spastic CP, Gross Motor Functional Classification System (GMFCS) level III, completed a six-week exergame programme. Outcomes were obtained at baseline and post-intervention. The primary outcome measure was the GMFCS III-specific shuttle run test (SRT-III). Secondary outcomes included health-related quality of life (HQL) as measured by the KIDSCREEN-52 questionnaire, six-minute walk test, Wingate arm cranking test and anthropomorphic measurements. Results : There were significant improvements in the SRT-III ( t = −2.5, p = 0.04, d = 0.88) post-intervention. There were no significant changes in secondary outcomes. Conclusion : An exergame cycling programme may lead to improvement in cardiovascular fitness in youth with CP. This study was limited by small sample size and lack of a comparison group. Future research is warranted.